Postoperative Complications in Post-Tonsillectomy Patients Without Post-Operative Antibiotics - Dongol, Suman Raj; Mahaseth, Rajeev Kumar; Bista, Ranishma; KC, Sarita (Medical Journal of Shree Birendra Hospital, 2023)
Introduction: Empirical use of antibiotics has tremendous effects in the health sector in terms of medical expenses and antibiotic resistance. Current guidelines do not recommend antibiotic use post tonsillectomy however, some surgeons prefer antibiotic use in the post-operative period. This study aims to evaluate post-operative findings such as haemorrhage and fever in patients without the use of post-operative antibiotics. Methods: This was a descriptional retrospective study conducted with chart review of medical records of the patients operated and not receiving post tonsillectomy antibiotics at the Department of ENT, Head and Neck Surgery, Shree Birendra Hospital, Chhauni, Kathmandu, Nepal. The post-tonsillectomy findings such as hemorrhage and fever were recorded and analyzed. Results: There were a total of 146 patients (87 males and 59 females) aged four to 72 years with a mean age of 26.76 ± 12.07 years during the study period. Haemorrhage was seen in eight (5.4%) patients. Two had primary haemorrhage and six had secondary haemorrhage. There was fever among seven patients (4.79%) out of which three had developed fever on 1st postoperative day (POD), two on second, one on fifth and one on eighth post operative day. Conclusion: Post-tonsillectomy morbidity such as haemorrhage and fever were minimal in patients without post operative antibiotics.